TOXICITY OF COPPER ON THE PROTEIN CONTENT OF CERTAIN TISSUES OF FRESHWATER FISH, CHANNA GACHUA (HAM) - S. J. KAWADE; Y. K. KHILLARE (The Bioscan, 2012)
Industrial effluent containing heavy metals, on entering aquatic environment causes biochemical disturbances in the fish. The present study deals with the toxicity of copper as (CuSO4), as a component of industrial waste and its effect on tissue protein at 24, 48, 72 and 96h. The LC50 values were found at 180 ppm, 88 ppm, 40 ppm and 20 ppm for 24, 48, 72 and 96h respectively. The estimated protein concentration in the tissues-gills, liver, kidney, ovary and testis were found to be reduced during the exposure periods. Maximum reduction in protein level in the tissues was found at 96h.